Long-term dynamics of forests with Pinus sibirica in the upper reaches of the River Kolva (Northern Pre-Urals, Russia) from 1938 to 2023 - Alexei A. Aleinikov; Vadim E. Aleksutin; Foma K. Vozmitel; Alexey N. Gunya (Nature Conservation Research: Заповедная наука)
Forest ecosystems have been impacted by human activity over several millennia in a variety of ways. Previous land use activity has not only changed the ratio of various terrestrial ecosystems, but also influenced the distribution of tree species. The insight into the forest species composition, dynamics and revealing how it differs from the modern one should be of decisive importance for the identification and conservation of the most valuable forests, as well as the restoration of ones previously disturbed. The density and distribution of some species continues to decline rapidly due to the anthropogenic activity. This problem is most urgent in boreal forests, formed by a limited set of tree species. Studies of the long-lived tree species dynamics and their ability to restore after various types of disturbances deserve special attention. Based on analysis of forest management materials from 1938 and 2023, this paper was aimed to analyse the dynamics of forests with the participation of Pinus sibirica in the Northern Pre-Urals (Permsky Krai, Russia), on the western border of the species' natural range. In 1938, the forests with Pinus sibirica occupied 16.6% of all forests in the research area. In 1938, most forests with Pinus sibirica (64%) were forests, in which P. sibirica was represented by only 1–5% of the stock. Pinus sibirica-dominated forests were almost absent, with only one site with 60% dominance of P. sibirica, and five sites with 40% dominance of P. sibirica. Over the next 85 years, the area of forests with Pinus sibirica participation in the research area has decreased by 2.5 times due to the impact of clear cuttings and forest fires. By 2023, the ratio of forest areas with various proportions of Pinus sibirica participation had changed considerably. The highest changes were found in forests with Pinus sibirica participation of 1%, 5% and 20% of the stock. Analysis of the typological structure of forests showed that at present Pinus sibirica has survived only in natural dark-coniferous forests, which have not been affected previously by forestry activities and fires. Due to the exceptionally slow regeneration following fires and logging activities, Pinus sibirica is absent in the forests formed over the studied period. The current federal legal restrictions prove ineffective as they target the preservation of forest stands containing over 30% of Pinus sibirica, while the majority of forests in the study area contain less proportion of this species. We believe that it is necessary to develop uniform measures to preserve existing and restore the lost Pinus sibirica populations in the Komi Republic and the Permsky Krai, including the prohibitions on the logging of forests with any proportion of Pinus sibirica as well as the creation of P. sibirica forest plantations.